Limed in sandy soils for soybean cultivation: A mini-review - Rodrigues, Mateus Borges; Pinotti, Carla Regina (Brazilian Journal of Science, 2024)
Liming is the method in which limestone is applied to regulate the pH of the soil reducing its acidity and making the minerals labile. This study aimed to evaluate the management of liming using dolomitic limestone in sandy textured soils, on the development of soybean cultivation through a bibliographical survey. Sandy soil also, known as “light soil” is largely composed of sand and a smaller proportion of clay around 70% and 15% respectively, its grain size is higher, and the presence of nutrients is very scarce. Correcting soil acidity through liming is the first step towards obtaining a considerably productive crop, especially in recently cleared areas. Since in acidic soils, the limitation to plant development arises mainly from the indirect effects of pH. Therefore, it is necessary to analyze the soil continuously as well as the weather conditions in order to obtain the desired result. Several results have been observed in which the use of liming in acidic soils, mainly in the Brazilian Cerrado, reduces the toxic action of aluminum on the plant and promotes greater absorption of nutrients and micronutrients for the plants, in addition to maintaining the soil microbiota.